Isohexide-diacetal based polymers and a process thereof - Chikkali, Samir H.; Rajput, Bhausaheb S. (WO/2014/181358, 2014)
The present invention discloses isohexide based compounds and their polymers which are derived from renewable resources and are potentially degradable. Also disclosed herein is the synthesis of isohexide based monomers and their polymers from renewable resources which are potentially degradable. Further, the present invention disclose a process for the synthesis of isohexide based copolymers via copolymerization of isohexide based monomers and long chain diols, which are degradable. (FR)Cette invention concerne des composés à base d'isohexide et leurs polymères qui sont dérivés de ressources renouvelables et sont potentiellement dégradables. Cette invention concerne également la synthèse de monomères à base d'isohexide et leurs polymères à partir de ressources renouvelables qui sont potentiellement dégradables. Un procédé de synthèse de copolymères à base d'isohexide par copolymérisation desdits monomères à base d'isohexide et de diols à chaîne longue, qui sont dégradables, est en outre décrit.

Insertion copolymerization of difunctional polar vinyl monomers with ethylene - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Chikkali, Samir H. (ACS Macro Letters, 2015)
A single-step synthesis, structural characterization and application of a neutral, acetonitrile ligated, palladium-phosphinesulfonate complex [{P<\^>O}PdMe(L)] (P<\^>O = K-2-P,O Ar2PC6H4SO2O with Ar = 2-MeOC6H4; L = CH3CN) (3) in coordination/insertion copolymerization of ethylene with difunctional olefin is investigated. In a significant development, complex 3 was found to catalyze insertion copolymerization of industrially relevant 1,1-disubstituted difunctional vinyl monomers for the first time. Thus, insertion copolymerization of ethyl-2-cyanoacrylate (ECA or super glue) and trifluoromethyl acrylic acid (TFMAA) with ethylene produced the corresponding copolymers with 6.5% ECA and 3% TFMAA incorporation. Increasing the concentration of difunctional olefins led to higher incorporation but at the expense of lower activities. These observations indicate that complex 3 tolerates difunctional vinyl monomers and provides direct access to difunctional polyolefins that have not been attempted before.

Impact of modular substitution on crystal packing: the tale of two ureas - Koshti, Vijay S.; Thorat, Shridhar H.; Gote, Ravindra P.; Chikkali, Samir H.; Gonnade, Rajesh G. (CrystEngComm, 2016)

Isomerizing hydroformylation of cashew nut shell liquid - Pandey, Swechchha; Shinde, Dinesh R.; Chikkali, Samir H. (ChemCatChem, 2017)
A small library of bisphosphorus ligands was evaluated in the rhodium-catalyzed isomerizing hydroformylation (I-HF) of cashew nut shell liquid (CNSL). The rhodium complex of 1,2-bis((di-tert-butylphosphanyl)methyl)benzene (BDTBPMB; L4) outperformed the other bisphosphite and bisphosphine ligands and unveiled a moderate selectivity of 28% and 50% in the I-HF of CNSL monoene and methoxy-protected monoene, respectively. The resultant aldehyde 16-(3-methoxyphenyl)hexadecanal P1 was isolated and its identity was fully established. Application of bis-phosphine ligand L4 in the I-HF of highly challenging CNSL cardanol (S3) and methoxy-protected CNSL cardanol yielded a linear selectivity of 74%, although with reduced conversion. To demonstrate the synthetic utility of our strategy, the obtained aldehyde (derived from S3) was subjected to hydrogenation and the resultant 3-(16-hydroxyhexadecyl) phenol (P8) was isolated in 89% isolated yield. High-pressure NMR investigation revealed selective formation of a bis-equatorial BDTBPMB-rhodium complex, which might be responsible for the excellent linear selectivity.

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Insertion copolymerization of functional olefins: Quo Vadis? - Birajdar, Rajkumar S.; Chikkali, Samir H. (European Polymer Journal, 2021)
Functional polyethylene is a specialty polymer with unique set of properties and caters to a niche market. Currently, it is manufactured using high-pressure, high-temperature radical polymerization, or post-reactor (indirect) modification methods. Insertion copolymerization of functional olefins with ethylene provides a low pressure, direct route to prepare functional polyethylenes. However, insertion copolymerization of functional olefins with ethylene poses several impediments and requires special considerations. This review presents the current strategies, examines the progress, and attempts to gauge the commercial potential of direct synthesis of functional polyethylene. The performance of late transition metal catalysts derived from a-diimine, imine-phenolate, phosphine-sulfonate, bis-phosphine-mono-oxide, carbene-phenolate, phosphine-phenolate and their derivatives in the insertion copolymerization of functional olefins with ethylene is evaluated. While catalyst designing is crucial, incorporation of polar olefins that can serve an additional purpose is equally important. Therefore, we have organized the review in the following sections, polar alkenes with- acrylates, acrylic acids, acetates, nitriles, ethers, halides, two functional groups, cross-linking groups, dynamic interactions/self-healing properties, additional function/purpose, renewable functional olefins, and examine the progress. Among these, acrylates have been most intensively investigated and have been successfully incorporated in the polyethylene main-chain. Ethylene, methyl acrylate copolymers prepared by direct copolymerization reveal comparable melting temperature to that of LLDPE (at similar co-monomer content) and unfold the commercial potential of these materials. Recent developments on the insertion copolymerization of renewable functional olefins and di-functional olefins have elicited significant interest. This strategy is being viewed as a means of reducing environmental impact and enabling high functional group density at the same extent of incorporation. The overview thus offers a succinct account of insertion copolymerization of functional olefins, sheds light on the copolymer microstructure/material properties, and initiates a discussion on the commercial potential of functional polyethylene.
Keywords: Catalyst; Functional polyethylene; functional polyolefins; Hydrophilic polyethylene; insertion copolymerization; Polyethylene

Iron-catalysed highly selective hydroalkoxycarbonylation of alkynes using CO as C1 source - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (Catalysis Science & Technology, 2023)
Though precious and rare, late-transition metals have been extensively used in metal-catalysed carbonylation reactions in organic transformations. On the other hand, base metals are abundant and cheap, but their practical utilization in carbonylation reactions is rarely explored. Here, we report iron-catalysed hydroalkoxycarbonylation of alkynes to alpha,beta-unsaturated esters in one pot. A readily available iron precursor [Fe2(CO)9] in the presence of a diimine ligand L7 catalyzes the conversion of alkynes to alpha,beta-unsaturated esters under 10 bar CO pressure. This operationally simple protocol tolerates various functional groups and allows facile access to about 40 alpha,beta-unsaturated esters. The synthetic utility of the reaction has been demonstrated by scaling up the reaction to 1 g and by preparing sunscreen/antifungal agents. The kinetic study suggests that the reaction is an approximate 1st order with respect to the iron catalyst, and the initial rate of the reaction is 3.6 x 10-2 M h-1. Mechanistic investigations using NMR spectroscopy indicated the existence of an [Fe-H] intermediate, and control experiments using a radical trapping reagent and EPR revealed the absence of any radical species in the reaction. Precious and rare, late transition metals have been extensively used in carbonylation. An earth abundant iron-catalyst is reported here for hydroalkoxycarbonylation of alkynes in the presence of CO as C1 source.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Iron-catalyzed chemoselective reduction of enimines to N-Allylic amines via hydrosilylation - Tewari, Tanuja; Shaikh, Maulali H.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2025)
Chemoselective hydrosilylation of unsaturated imines is challenging as the two double bonds compete for the reaction. Here in, we report an iron-catalyzed chemoselective hydrosilylation of enimines leading to the generation of allyl amines in the presence of phosphine ligand. A low-valent Fe(0) complex [(BDA)Fe(CO)3] catalyzed the hydrosilylation of enimine at room temperature and exhibited broad substrate scope including a variety of enimine (cinnamylimine, allylimine) and ketimine. Mechanistic investigations revealed that the reaction proceeds through an oxidative addition of the silane compound, leading to the formation of an iron hydride intermediate. Subsequently, a two-electron pathway facilitates the hydrosilylation of the enimine substrate. This has been supported by preparing a well-defined Fe(II)-silane complex and using it as a catalyst control. Based on experimental and computational investigations, a plausible Chalk-Harrod-type mechanism is proposed.
Keywords: Cinnamyl amine; Imine hydrosilylation; iron catalysis; Iron hydride; Phosphine